Impact of Artificial Intelligence on Smart Cities - Mohammad Ilyas (Journal of Systemics, Cybernetics and Informatics)

(untitled)
A smart city makes use of available technologies to improve the efficiency of its operations and enhance the quality of life of its citizens. The technologies that have had and continue to have a significant impact on smart cities include hyperconnected networks such as the Internet of Things (IoT) and artificial intelligence (AI). AI is increasingly becoming involved in all aspects of human existence. Many see the emergence of AI as a revolution that will impact every aspect of our lives. Some see it as an evolution based on the recent advances in powerful computational platforms, and access to massive amounts of data. IoT provides an elaborate platform for collecting data from various applications. AI can analyze this data and make intelligent decisions enabling the development of smart systems. This combination is leading to the rapid development of smart systems. These systems include smart healthcare, smart transportation, smart energy, smart agriculture, and many more, addressing the needs of smart cities. Using these technologies in smart cities will certainly promote cohesive, connected, healthier, and happier communities. This paper examines the current state of AI in smart cities and discusses potential AI applications for the further development of smart cities.